Microperimetric evaluation and predictive factors of visual recovery after successful inverted internal limiting membrane-flap technique for macular hole in high myopic eyes - Sborgia, Alessandra; Boscia, Giacomo; Niro, Alfredo; Landini, Luca; Pastore, Valentina; Albano, Valeria; Piepoli, Marina; Donghia, Rossella; Dore, Stefano; Viggiano, Pasquale; Buonamassa, Rosa; Di Pardo, Camilla; et al. (Frontiers in Medicine, 2023)
Inverted Internal Limiting Membrane (ILM)-flap technique demonstrated its effectiveness, in terms of anatomical closure rate and visual acuity recovery for high myopic macular holes. We evaluated macular function after a successful inverted ILM-flap for macular holes in high myopic eyes (hMMH) using microperimetry to predict visual prognosis. A retrospective study on 23 eyes of 23 patients after surgical closure of hMMH, was performed. All patients underwent inverted ILM-flap and gas tamponade. Cataract surgery was performed in phakic eyes. Study outcomes including best-corrected visual acuity (BCVA), retinal sensitivity (RS) at central 12°, central retinal sensitivity (CRS) at central 4° and mean deviation (MD), and fixation behavior as bivariate contour ellipse area (BCEA, degrees2) measured by microperimetry, were evaluated over 6 months. A mixed-effects model was used to evaluate and compare the repeated measurements of outcomes between phakic and pseudophakic eyes. A regression model was performed to assess the relationship between BCVA at 6 months and independent variables. Overall mean BCVA improved from 0.98±0.21 logMAR at baseline to 0.47±0.31 logMAR at the last follow-up (p<0.001). Over 6 months, overall sensitivity measurements improved (RS, p=0.001; CRS, p<0.0001; MD, p=0.03), and the BCEA decreased in dimension, although not significantly (p≥0.05). The mixed model revealed a significantly better effect of inverted ILM-flap combined with cataract surgery on BCVA and CRS in phakic eyes than inverted ILM-flap alone in pseudophakic ones. The regression model revealed a relationship of 6-month BCVA with pre-operative BCVA (β=0.60, p=0.02) and RS (β=-0.03, p=0.01). The inverted ILM-flap technique significantly improved visual acuity and retinal sensitivity after the hMMH closure, particularly when combined with cataract extraction. Pre-operative visual acuity and retinal sensitivity at central 12° may predict post-surgical visual acuity.